From Public Opinion to Digital Resistance: The Role of Social Media in Contesting Government Policies - I Gusti Ngurah Parthama; I Wayan Pastika; I Made Netra; I Nyoman Aryawibawa (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The rise of social media has significantly transformed public discourse. It allows individuals to engage in political discussions, express opinions, and challenge governmental narratives. Unlike traditional media, social media platforms facilitate interactive and participatory engagement. Users can respond to official statements in real time. This study examines user comments on Kompas Facebook post regarding the Indonesian government’s response to the Covid-19 pandemic. Analyzing the discourse within these comments, the research explores functions of social media as a platform for democratization, power resistance, two-way communication, and alternative discourse formation. This study employs qualitative content analysis and critical discourse analysis (CDA). It is used to categorize and interpret user comments. The data included diverse linguistic strategies such as support, criticism, sarcasm, rhetorical questions, and religious expressions. Those were systematically coded to identify emerging themes. The findings reveal that social media enables democratic participation. It is also characterized by polarization of discourse and performative engagement. The interaction between government narratives and user responses demonstrates that social media facilitates counter public discourse, ideological contestation, and user-driven political deliberation. The study concludes social media that serves as a dynamic space for political communication where institutional narratives are actively contested. However, the limited presence of constructive suggestions highlights the challenges of fostering substantive policy discussions in digital spaces. By bridging discourse analysis, media studies, and political communication, this research provides a novel contribution to understanding digital discourse dynamics in contemporary political engagement.